The Effect Of E-Service Quality on Repurchase Intention With E-Customer Satisfaction as An Intervening Variable - Putranto, Ahnaf Raka; Handrito, Radityo Putro (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to assess the effects of e-service quality on the repurchase intention of Tokopedia e-commerce users in Jawa with e-customer satisfaction as the intervening variable. In this explanatory study, hypotheses related to various variables were tested to determine any causal relationship. The data was harvested via online questionnaires distributed to 312 respondents and was examined through Partial Least Squares in Smart PLS 4.0. The results suggest that e-service quality significantly influences repurchase intention, that e-service quality significantly affects e-customer satisfaction, and that e-customer satisfaction mediates the impacts of e-service quality on the repurchase intention of Tokopedia e-commerce users in Jawa.